KEHILANGAN AIR DAN PENAMBAHAN PADATAN YANG TERJADI SELAMA PROSES DEHIDRASI OSMOTIK BUAH NAGA - If'all; Spetriani; Siti Fathurahmi (Fakultas Pertanian Universitas Alkhairaat Palu, 2020)
Osmotic dehydration is a method that can be used in the pretreatment of drying by immersing the material in a hypertonic solution. The purpose of this study was to examine the effect of concentration and temperature of the osmotic solution on water loss and solid gain to dragon fruit pieces during the osmotic dehydration process. Dragon fruit slices were immersed in osmotic solution with different concentration and temperature solution (30 oBrix, 50 oBrix, and 70 oBrix, as well as 30 oC, 40 oC, and 50 oC). The WL value for the concentration of 30 oBrix solution varies from 17.42% to 25.26%, for a 50 oBrix concentration is 32.84% to 50.38%, and for a 70 oBrix concentration is 39.89% to 57.99% . Thus, changes in the level of WL, concentration and temperature of the solution, where the higher the concentration and temperature of the solution, the greater the WL of the material. Meanwhile, for SG on materials, values ​​ranged from 2.092% -10.010%. Based on the calculation of the Azuara model, the WL values ​​ranged from 21.551% -75, 187% and 3.899% -17.575% for the SG value. The coefficient of determination for the calculation of the Azuara model is 0.938 - 0.992, thus the Azuara model can be said to be feasible for modeling the WL and SG values ​​on osmotic dehydration of dragon fruit.